آليات إصلاح وتطوير الجماعات الإقليمية في الجزائر - اسماعيل, فريجات (University of Eloued جامعة الوادي, 2020)
يعتبر تطوير وترقية نظام الجماعات الإقليمية تحديًّا مستمرا للدول والأفراد، لأجل بلوغ تحقيق أهدافه الإدارية والسياسية، ليصبح مسألة معالجة أوجه قصوره وإزالة العقبات المسببة لذلك أمرا ملحا وضروريا، وذلك ما يصيبه من سوء تنظيم أو ترهل وقدم، فيفقد قدرته على مجابهة حاضره أو استعداده لمستقبله أو مجاراته. تحتاج الجماعات الإقليمية إلى إعادة النظر في كافة أنظمتها وما يتعلق بمحيطها، بذلك يستلزم إدخال إصلاحات وتحسينات في إطارها القانوني لجعله يتماشى والمبادئ المتجددة للامركزية الإقليمية والمرفق العام، كما هي في حاجة لأن تكون إطارا وفضاء تشاركيا بامتياز. لترقية أدائها أو في جوانبها الوظيفية لا بدا من تعزيز الوسائل القانونية، المالية، البشرية، والتقنية، كمتطلبات إصلاحية ضرورية ومرتكزات ترتفع بها مكانتها كإدارة جوار وقرب. the development and the promotion of the local authority system is considered as an on going challenge for individuals and states for getting and achieving its administrative and political goals ,as a result the issue of addressing the system shortcomings (lack of organization,to slim down,oldness)has become an urgent and nessecery thing ,to avoid losing its capacity to confrontate the present or its readiness for its futur the regional community needs to reviewing all its systems and everything concerning the local authority perimeter. Accordingly,it must introduce reforms and improvement in the legal frame work of the regional community for make it in line with the new principles for regional decentralization and the puplic utility as well ashe local authority needs to be a participatory space and framework par excellence. It is nessacery the strenghtening the legal means of local authority to promote its working as important requirements and stepping stones towards increasing of its position to manage tha neighbourhood and proximity.
مجلد11، عدد1
Keywords: إصلاح الجماعات الإقليمية ; تطوير الجماعات الإقليمية ; التنمية المحلية ; المجالس الشعبية المحلية ; البلدية ; الولاية; Reforming the Territorial Collectivities; Development of the Territorial Collectivities; Sustainable Development; Townhall; State; Local People's Councils.